2000
DOI: 10.1016/s0928-8244(99)00194-7
|View full text |Cite
|
Sign up to set email alerts
|

The pattern and level of cytokines secreted by Th1 and Th2 lymphocytes of syphilitic patients correlate to the progression of the disease

Abstract: The results of our previous work indicated that cell-mediated immune response, of importance in protection against Treponema pallidum, is distinctly inhibited at certain periods of syphilitic infection. Considering that cytokines, produced by Th1 lymphocytes, take part in this response and that their secretion may be regulated by cytokines of Th2 lymphocytes, we examined if, and in which stages of syphilis, such a regulation may exist. In this study we have examined the ability of cells to produce IL-2, IFN an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…4,7,13 Some studies suggest that eosinophil attractant cytokines play a role in these non-hypersensitivity phenomena. 12,14 Eosinophilic dermatosis of hematologic malignancy is a rare skin disease associated with chronic lymphocytic leukemia, which shows perivascular inflammation with increased eosinophils and mimics an insect bite. 13 Davis et al showed enhanced eosinophil survival in culture in the presence of tissue extracted from eosinophilic dermatosis of hematologic malignancy, indirectly revealing the presence of eosinophil attractant cytokines within lesions.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,13 Some studies suggest that eosinophil attractant cytokines play a role in these non-hypersensitivity phenomena. 12,14 Eosinophilic dermatosis of hematologic malignancy is a rare skin disease associated with chronic lymphocytic leukemia, which shows perivascular inflammation with increased eosinophils and mimics an insect bite. 13 Davis et al showed enhanced eosinophil survival in culture in the presence of tissue extracted from eosinophilic dermatosis of hematologic malignancy, indirectly revealing the presence of eosinophil attractant cytokines within lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, if suppression of DTH is induced by AIDS or other induced immunosuppression (252), latency can be terminated more rapidly, and can be succeeded by a systemic infection that requires treatment with high doses of penicillin. In tertiary syphilis, studies of Th1 and Th2 cytokine production by lymphocytes demonstrated low Th1 cytokine production (cellular immunity) and high Th2 cytokine production (non-complement, fixing antibody response) (253). The authors propose that this cytokine imbalance is one of the reasons why T. pallidum multiplication and development of lesions occur in tertiary syphilis (253).…”
Section: Immune Deviation: a Comparison Of Syphilis And Leprosymentioning
confidence: 99%
“…In tertiary syphilis, studies of Th1 and Th2 cytokine production by lymphocytes demonstrated low Th1 cytokine production (cellular immunity) and high Th2 cytokine production (non-complement, fixing antibody response) (253). The authors propose that this cytokine imbalance is one of the reasons why T. pallidum multiplication and development of lesions occur in tertiary syphilis (253). …”
Section: Immune Deviation: a Comparison Of Syphilis And Leprosymentioning
confidence: 99%
“…Thus, it is likely that the mutants harboring M184V were derived from latently infected reservoir cells which had been established while the patient had taken 3TC without NNRTI. Syphilis infection may have predisposed the reactivation of these proviruses [10,27].…”
Section: Discussionmentioning
confidence: 99%